Natural products targeting cellular processes common in Parkinson's disease and multiple sclerosis - Xu, Xuxu; Han, Chaowei; Wang, Pengcheng; Zhou, Feimeng (Frontiers in Neurology, 2023)
The hallmarks of Parkinson’s disease (PD) include the loss of dopaminergic neurons and formation of Lewy bodies, whereas multiple sclerosis (MS) is an autoimmune disorder with damaged myelin sheaths and axonal loss. Despite their distinct etiologies, mounting evidence in recent years suggests that neuroinflammation, oxidative stress, and infiltration of the blood-brain barrier (BBB) all play crucial roles in both diseases. It is also recognized that therapeutic advances against one neurodegenerative disorder are likely useful in targeting the other. As current drugs in clinical settings exhibit low efficacy and toxic side effects with long-term usages, the use of natural products (NPs) as treatment modalities has attracted growing attention. This mini-review summarizes the applications of natural compounds to targeting diverse cellular processes inherent in PD and MS, with the emphasis placed on their neuroprotective and immune-regulating potentials in cellular and animal models. By reviewing the many similarities between PD and MS and NPs according to their functions, it becomes evident that some NDs studied for one disease are likely repurposable for the other. A review from this perspective can provide insights into the search for and utilization of NPs in treating the similar cellular processes common in major neurodegenerative diseases.